2019
DOI: 10.1609/aaai.v33i01.33011949
|View full text |Cite
|
Sign up to set email alerts
|

A Bridge between Liquid and Social Welfare in Combinatorial Auctions with Submodular Bidders

Abstract: We study incentive compatible mechanisms for Combinatorial Auctions where the bidders have submodular (or XOS) valuations and are budget-constrained. Our objective is to maximize the liquid welfare, a notion of efficiency for budget-constrained bidders introduced by Dobzinski and Paes Leme (2014). We show that some of the known truthful mechanisms that bestapproximate the social welfare for Combinatorial Auctions with submodular bidders through demand query oracles can be adapted, so that they retain truthfuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Xiao [2015, 2017] extended and also generalized the work of Dobzinski and Paes Leme [2014]. Fotakis et al [2019] showed how truthful auctions which approximate the social welfare in submodular valuation se ings without budget constraints can be adapted to se ings with budget constraints, so that they remain truthful and also now achieve almost the same approximation for the liquid welfare. In a slightly different context, Brânzei et al [2017] viewed the liquid welfare as an upper bound on the maximum possible revenue and designed truthful mechanisms for revenue maximization, while Brânzei and Filos-Ratsikas [2019] studied similar questions for the best-response dynamics in games induced by envy-free pricing mechanisms.…”
Section: Other Related Workmentioning
confidence: 99%
“…Xiao [2015, 2017] extended and also generalized the work of Dobzinski and Paes Leme [2014]. Fotakis et al [2019] showed how truthful auctions which approximate the social welfare in submodular valuation se ings without budget constraints can be adapted to se ings with budget constraints, so that they remain truthful and also now achieve almost the same approximation for the liquid welfare. In a slightly different context, Brânzei et al [2017] viewed the liquid welfare as an upper bound on the maximum possible revenue and designed truthful mechanisms for revenue maximization, while Brânzei and Filos-Ratsikas [2019] studied similar questions for the best-response dynamics in games induced by envy-free pricing mechanisms.…”
Section: Other Related Workmentioning
confidence: 99%